2014
DOI: 10.1097/wnr.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture-induced changes in functional connectivity of the primary somatosensory cortex varied with pathological stages of Bell’s palsy

Abstract: Bell’s palsy is the most common cause of acute facial nerve paralysis. In China, Bell’s palsy is frequently treated with acupuncture. However, its efficacy and underlying mechanism are still controversial. In this study, we used functional MRI to investigate the effect of acupuncture on the functional connectivity of the brain in Bell’s palsy patients and healthy individuals. The patients were further grouped according to disease duration and facial motor performance. The results of resting-state functional MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…It has been verified that the acupuncture played an important role in ameliorating the blepharospasm in non-lesioned side [15,16]. We suggested that the alteration in non-lesioned side SI connectivity might be the result of reductions of the abnormal brain activity tendencies [5,10].…”
Section: The Possible Mechanism Of Bilateral Si Connectivity Changesmentioning
confidence: 98%
See 4 more Smart Citations
“…It has been verified that the acupuncture played an important role in ameliorating the blepharospasm in non-lesioned side [15,16]. We suggested that the alteration in non-lesioned side SI connectivity might be the result of reductions of the abnormal brain activity tendencies [5,10].…”
Section: The Possible Mechanism Of Bilateral Si Connectivity Changesmentioning
confidence: 98%
“…Our previous studies have also shown that the acupuncture leads to significant connectivity change. In addition, several investigations suggest the brain's responses to acupuncture depend on the functional connectivity status and that some functional reorganizations of special cortical regions are important in the process of BP recovery [5,9,10]. Thus, we believed that different effects of acupuncture made on the bilateral Hegu points would be revealed by comparing functional connectivity alterations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations